Maximizing Economic Efficiency in Urban Mustard Farming through Pipe, Soil, and Bottle-Based Systems - Prawitasari, Putu Putri; Rafa Nafisah, Ghalda Syadza; Nurmalasari, Made Ratih; Ari Krismajayanti, Ni Putu; Megawati, Ida Ayu Putu (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Urban agriculture has gained recognition as an effective solution to urbanization's challenges, including food security and environmental sustainability. This study, "Maximizing Economic Efficiency in Urban Mustard Farming through Pipe, Soil, and Bottle-Based Systems," focuses on the innovative use of recycled materials such as plastic bottles and pipes to create sustainable farming systems in urban environments. The research highlights the integration of these materials to maximize space and resources, enabling efficient mustard greens cultivation in limited urban areas. In Peguyangan Village, Bali, this community service program aimed to educate residents on utilizing plastic waste as a resource for urban farming. By conducting hands-on training, participants learned how to build and maintain planting systems using recycled pipes and bottles, which improved soil moisture retention and reduced water consumption. As a result, the local community adopted more sustainable farming practices, reducing plastic waste and enhancing crop yields. The program's success is evident in the increased participation of residents, with active collaboration between students, community members, and local officials. This initiative not only raised awareness of sustainable agriculture but also provided practical skills to residents, fostering a sense of community and environmental responsibility. The project serves as a model for promoting urban farming and resource efficiency in densely populated areas.